The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001 (Trichoptera: Hydropsychidae), endemics of Crete (South Aegean, Greece), with notes on their ecology - Karaouzas, Ioannis (Zootaxa, 2016)
The larvae of Hydropsyche rhadamanthys Malicky 2001 and Hydropsyche sarpedon Malicky 2001, endemics of Crete Island, Greece, are described for the first time. The diagnostic features of the species are described and illustrated, and some information regarding their ecology is included. In addition, diagnostic characters for larvae of the known Aegean Hydropsyche species are provided.